Dampak liberalisasi finansial Indonesia dan Korea Selatan terhadap perekonomian: Sebuah studi komparasi - M. B. Hendrie Anto (Universitas Islam Indonesia, 2000)
Economy recovery in Indonesia is a little slower than that of Korea. One important factor of the problem is the condition of financial sectors where the financial sector in Korea is healthier than that of Indonesia. Theoretically, there is a controversy of contribution the financial sector on economy.